2001
DOI: 10.1136/jnnp.70.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Detection of subarachnoid haemorrhage with magnetic resonance imaging

Abstract: Objectives-To measure the sensitivity and specificity of five MRI sequences to subarachnoid haemorrhage. Methods-Forty one patients presenting with histories suspicious of subarachnoid haemorrhage (SAH) were investigated with MRI using T1 weighted, T2 weighted, single shot fast spin echo (express), fluid attenuation inversion recovery (FLAIR), and gradient echo T2* sequences, and also by CT. Lumbar puncture was performed in cases where CT was negative for SAH. Cases were divided into acute (scanned within 4 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(92 citation statements)
references
References 11 publications
1
88
0
3
Order By: Relevance
“…13,14 T2* is considered useful for the diagnosis of subacute or chronic SAH. 6,16 This sequence appears effective in detecting a prior SAH indicating the location of a ruptured aneurysm. 16 On T2* images, SAH signal is dependent on the state of oxygenation and the integrity of red blood cell walls.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 T2* is considered useful for the diagnosis of subacute or chronic SAH. 6,16 This sequence appears effective in detecting a prior SAH indicating the location of a ruptured aneurysm. 16 On T2* images, SAH signal is dependent on the state of oxygenation and the integrity of red blood cell walls.…”
Section: Figmentioning
confidence: 99%
“…13,14 T2* gradient-echo sequences are useful for subacute or chronic SAH depiction. 6,15,16 Susceptibility-weighted imaging uses tissue magnetic-susceptibility differences to generate a unique contrast, based on a 3D flow-compensated gradient-echo sequence. 17 Previous studies have suggested that SWI could accurately detect small amounts of SAH and intraventricular hemorrhage (IVH).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] Bu konuda yapılan çok fazla çalışma olmasa da mevcut çalışmalar, anestezi altındaki hastalarda gözlenen HSA için başlıca iki faktörün sorumlu olabileceğini ileri sürmektedirler: kullanılan anestezik maddeler ya da anestezi/sedasyon sırasında hastaya uygulanan oksijen. Bugüne kadar gerçek-leştirilen çalışmalar incelendiğinde, çoğunda anestezi yönteminin standardize edilmemiş olduğu göze çarpmaktadır.…”
Section: -5unclassified
“…MRI offers a higher sensitivity to detect SAH in patients presenting outside of first 48 hours after onset; however MRI is not readily available at most institutions and some patients may not be suitable for MRI. The FLAIR (fluid attenuated inversion recovery) and GRE (gradient echo) sequences are the most reliable method for detection of SAH in MRI [16].…”
Section: Neuro-imagingmentioning
confidence: 99%